Перелет птиц через Черное море - Кистяковский, А.Б. (Вестник зоологии, 1967)
As resulted from observations, birds fly across the Black Sea with fair wind. Some of them fly low over water, but small passerine birds seem to cross the sea at a height of some hundred metres. Even Ralli which fly badly cross the Black Sea without stopping in the widest place.